Dynamics of Friction Processes on Stainless Steel AISI 201 with Coarse and Ultrafine-Grained Structure; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Vorontsov A. V.; Filippov A. V. Andrey Vladimirovich; Tarasov S. Yu. Sergei Yulievich; Podgornykh O. A. Oleg Anatolievich; Shamarin N. N.; Filippova E. O. Ekaterina Olegovna (2018, 2018)
Title screen